Gestionar y parodiar el trabajo digno. Sobre la creación de alternativas a la prostitución para mujeres trans y sus complejidades - Cutuli, María Soledad (Revista de Antropología Social, 2022)
This paper aims to articulate political anthropology and gender studies, in order to address the tensions between prostitution and work in the organizational experience of trans women in the metropolitan area of ​​Buenos Aires, Argentina. Focusing on the daily life of one cooperative venture, we analyze the processes of institutionalization of these alternatives to prostitution for trans population. Based on the results of an ethnographic fieldwork developed between 2008 and 2012, we explore the tensions and meanings involved in the categories of work and dignity, through which the people involved processed their experiences